Creation of a two-dimensional conducting path based on the engineering oxidation state of WO 3 with Al 2 O 3 at the interface - Lee, Young Ahn; Kim, Jinseo; Lee, Sang Yeon; Park, Jucheol; Seo, Hyungtak (Applied Surface Science, 2019)
We report the dramatic manipulation of an oxide interface in Al 2 O 3 /WO 3 from insulating to metallic state by creating a two-dimensional conducting path. The WO 3 thin film is deposited on the SiO 2 grown Si substrate using radio frequency magnetron sputtering and the amorphous Al 2 O 3 layer is formed by atomic layer deposition on the WO 3 layer. After rapid vacuum annealing at 400 °C, the interfacial conducting path of Al 2 O 3 /WO 3 reveals an abnormally high sheet carrier density of 4.91 × 10 16 cm −2 compared with <10 9 cm −2 for bare WO 3 . The X-ray photoelectron spectroscopy (XPS) shows that WO 3 is partially reduced; and a W 5+ oxidation state is observed at the interface. The schematic electronic band diagram of the interfacial region obtained by combined XPS and ultraviolet photoelectron spectroscopy analyses indicates that the downward band bending at the surface of WO 3 induces a confined electron accumulation at the interface. Synergetic effects between the increased unpaired W 5d electrons in the W 5+ oxidation state and the accumulative charge confinement at the Al 2 O 3 /WO 3 interfaces lead to a two-dimensional conducting path. The metallic conduction is distinct from the insulating bulk properties. This study demonstrates an example of a short-range-ordered two-dimensional conducting path at two insulating oxide interfaces formed at low temperature, which is applicable to flexible oxide conductors with great conduction path stability.
Keywords: Al2O3; Bandbending; Charge confinement; Electron accumulation; Metallic conduction; Radio frequency magnetron sputtering; Sheet carrier densities; Short-range ordered; Al 2 O 3; Band bending; Interface; Reduction; WO 3